2015
DOI: 10.2147/opth.s57217
|View full text |Cite
|
Sign up to set email alerts
|

A review of the iStent® trabecular micro-bypass stent: safety and efficacy

Abstract: There is a significant demand for procedures that can effectively treat glaucoma with low risk and good visual outcomes. To fill this void, procedures termed “minimally invasive glaucoma surgery”, are gaining in popularity. This review will focus on the safety and efficacy of one such minimally invasive glaucoma surgery procedure, the trabecular micro-bypass stent. This stent is intended to lower intraocular pressure by directly cannulating Schlemm’s canal and thereby enhancing aqueous outflow. Recent randomiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 26 publications
0
23
0
1
Order By: Relevance
“…MIGS is intended to achieve lower IOP in patients with glaucoma with shorter surgical time, and ideally to achieve a medication sparing effect. All devices work by increasing the outflow of aqueous humor from the anterior chamber, either by directly accessing Schlemm’s canal 16 18 or shunting aqueous humor to the suprachoridal 19 or subconjunctival space. 20 Complications such as hypotony, hyphema, infections of the bleb, revisions of the bleb, and endophthalmitis may occur in up to 35% of patients treated with conventional glaucoma surgery, ie, trabeculectomy (TE).…”
Section: Introductionmentioning
confidence: 99%
“…MIGS is intended to achieve lower IOP in patients with glaucoma with shorter surgical time, and ideally to achieve a medication sparing effect. All devices work by increasing the outflow of aqueous humor from the anterior chamber, either by directly accessing Schlemm’s canal 16 18 or shunting aqueous humor to the suprachoridal 19 or subconjunctival space. 20 Complications such as hypotony, hyphema, infections of the bleb, revisions of the bleb, and endophthalmitis may occur in up to 35% of patients treated with conventional glaucoma surgery, ie, trabeculectomy (TE).…”
Section: Introductionmentioning
confidence: 99%
“…The suprachoroidal space (SCS) is a potential space found between the sclera and choroid. Due to its close proximity to the ciliary body, choroid, retina, and sclera, this space has recently drawn attention as a site for targeted drug delivery, 1 – 7 placement of glaucoma drainage devices, 8 11 and implantation of retinal prostheses. 12 As a site of drug administration, delivery into the SCS is noted for high bioavailability at targeted tissues in posterior segment diseases, as well as fast clearance by the choroidal vasculature.…”
mentioning
confidence: 99%
“…The Cypass (Transcend[56]) and iStent (Glaukos[57, 58]) micro-stent medical devices are used for lowering IOP in glaucoma refractory to medical therapy. They are surgically implanted within the SCS during cataract surgery using an ab interno approach.…”
Section: Accessing the Suprachoroidal Spacementioning
confidence: 99%
“…These studies also showed dose-sparing with SCS injection compared with eye drops. Micro-stents penetrated through the scleral spur to generate a fluid conduit from the anterior chamber into the SCS have been shown to reduce IOP in glaucoma patients[48, 57, 91]. …”
Section: Pharmacodynamicsmentioning
confidence: 99%